Описи стародавніх споруд Луцька у періодиці громадських товариств Правобережної України (остання третина ХІХ – початок ХХ ст.) - Zayets, Lubov; Заєць, Любов (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано публікації періодичних видань громадських товариств Правобережної України останньої третини ХІХ – початку ХХ ст., де наводяться огляди світських та церковних архітектурних пам’яток м. Луцька. Представлено матеріали про замок Любарта, церкву Іоана Богослова, єврейську синагогу, кафедральний католицький костел Св. Трійці.The article analyzes the published works in periodicals of public societies of the right -bank Ukraine in the last third of the 19-th century- the early 20-th century. These published works provide reviews of secular, defensive and ecclesiastical architectural monuments in Lutsk. The article provides the wide information about the Lubart’s castle, the Cathedral of St. John the Divine, the Jewish Synagogue, the Roman Catholic Church of the Holy Trinity, which represent the historical and artistic value.
The Descriptions of the Ancient Buildings of Lutsk in Periodicals of Public Societies in Right-Bank Ukraine (the last third of the 19-th century – the early 20-th century).
Keywords: Луцьк; стародавні споруди; періодичні видання; церква; замок; Lutsk; the ancient buildings; a periodical; a church; a castle